Pharmacology of Aging and Anti-Aging Effects of Phytochemicals in Skincare Using Carthamus Tinctorius L. Formulation - Md. Usman, Rageeb; Suresh Nair, Atullya; Qureshi, Naseem (Journal of Neonatal Surgery, 2025)
This research investigates the potential anti-aging effects of phytochemicals in skincare, with a focus on Carthamus tinctorius (safflower) as a key ingredient. Phytochemicals, plant-derived compounds, have garnered attention for their antioxidant, anti-inflammatory, and skin-protecting properties. This study aims to evaluate the effectiveness of Carthamus tinctorius extract in a formulated skincare product, assessing its ability to combat signs of aging, such as wrinkles, fine lines, and skin elasticity. Through laboratory experiments and clinical trials, the impact of the safflower extract on skin aging parameters will be analyzed. The findings suggest that safflower phytochemicals, particularly flavonoids and fatty acids, exhibit notable anti-aging benefits and could serve as an effective natural alternative in anti-aging skincare formulations.